If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -14 = -32 + 6x Reorder the terms: -14 + 3x = -32 + 6x Solving -14 + 3x = -32 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 3x + -6x = -32 + 6x + -6x Combine like terms: 3x + -6x = -3x -14 + -3x = -32 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + -3x = -32 + 0 -14 + -3x = -32 Add '14' to each side of the equation. -14 + 14 + -3x = -32 + 14 Combine like terms: -14 + 14 = 0 0 + -3x = -32 + 14 -3x = -32 + 14 Combine like terms: -32 + 14 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 24-m=2m | | -4.2x+31.5=-65 | | 7n-5=-29+4n | | 10w^2-57w+54=0 | | 210=x+3x-18 | | -3(4p+5)-2(3-14p)=3(8+5p) | | 9+19n-8=8n+86-6n | | 2g+4=1000 | | -5(x+3)+12=13-6x | | 45=28+x | | 10x^3+14x^2-16x= | | 4(0.8g+1.5)=2(3+1.6) | | 3x-36=2x+14 | | s+4=3 | | (5a^3-5a+2)(a-4)= | | x-6.84=4.9 | | 5(x+3)+12=13-6x | | (3x+9)+(3x+8)+(3x)=(3x)+(3x)+(4x+5) | | K-7=-13-2k | | 4t+9=(-8)-13 | | 242=x+5-22 | | 405xy+245x^2= | | 6x+308= | | 5x+6x+2+2=3x+5+7x | | -9x-13+11x-25=2 | | (-10)7= | | f(x)=3e^5x | | 100-2P=40+2P | | 100-2P=40 | | log(x+5)=ln(x-3) | | m^2-5m+14=0 | | 5(2x-8)-7x=x+6 |